THE EFFECTIVE WAYS TO TEACH LISTENING SKILLS TO BEGINNER LEVEL STUDENTS - Nurmamatova Nigora Farhod qizi; Boyqobilova Fazilat Ruzi qizi; Aʼzamova Marjona Panji qizi (Web of Journals Publishing, 2023)
This study aimed at identifying various ways and techniques during teaching listening to the beginners. Nowadays, most of the learners are facing with difficulties about understanding listening audio and podcasts. There are many methods identified by experts. The importance of contextualized activities, pre-listening activities, comprehension strategies, authentic listening materials, and visual support will be discussed. These strategies, supported by recent research findings, offer valuable insights for language educators seeking innovative and effective teaching techniques proficiency among beginner level students.
Keywords: listening ability, podcasts, group activity, methods, improvement, language mastering, pronounciation, beginner level students, contextualized activities, pre-listening activities, comprehension strategies, authentic listening materials, visual support.